2017
DOI: 10.1515/pthp-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

A Sorption Study between Ophthalmic Drugs and Multi Dose Eyedroppers in Simulated Use Conditions

Abstract: AbstractPreservative free ophthalmic formulations need to be packaged either as single doses, or using specially designed sterility preserving multidose eyedroppers. Our objective was to evaluate potential sorption phenomena between a device with a silicone sterility preserving membrane and the delivered drops of several ophthalmic solutions. Cyclosporine, rifamycin, latanoprost, timolol and norfloxacin were used as model drugs. Quantification of the active substance in deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…The influence of Zeta potential on sorption capacity was previously hypothesized [ 12 ], and this result was congruent with this previous finding as the closest to zero Zeta potential was responsible for the most important loss among PUR catheters. Silicone rubber is also known to present a risk of sorption [ 11 , 18 ]. Among all of the tested catheters, the silicone one appeared to have the highest tendency to induce diazepam sorption and was also correlated with a low surface Zeta potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of Zeta potential on sorption capacity was previously hypothesized [ 12 ], and this result was congruent with this previous finding as the closest to zero Zeta potential was responsible for the most important loss among PUR catheters. Silicone rubber is also known to present a risk of sorption [ 11 , 18 ]. Among all of the tested catheters, the silicone one appeared to have the highest tendency to induce diazepam sorption and was also correlated with a low surface Zeta potential.…”
Section: Discussionmentioning
confidence: 99%
“…Catheters are of tantamount importance as they are implanted through the skin into the blood circulation and actually administer the drugs into the patients’ body. Unfortunately, they are almost exclusively made of polyurethane (PUR) or silicone, and these materials, despite their great biocompatibility, have been shown to be at high risk of causing drug loss by sorption [ 13 , 14 , 15 , 16 , 17 , 18 ], but these studies are few, not recent, and do not take into account the whole infusion setup.…”
Section: Introductionmentioning
confidence: 99%
“…During the simulated use study, atropine was quantified in the emitted drops to evaluate any potential loss of API by sorption (adsorption or absorption), as it has been shown that such a phenomena can occur during the first few days of treatment initiation with certain APIs and ophthalmic delivery devices [ 49 ]. During the 6-day study, atropine concentrations in the emitted drops remained stable (no variation exceeding of ±5% of initial concentration), therefore excluding any clinically significant loss of atropine.…”
Section: Discussionmentioning
confidence: 99%
“…During the simulated test, the overall concentrations remained stable, yet variations in tacrolimus concentrations were observed in the emitted drops, especially with the 0.2 mg/mL formulation. This could be attributed to the sorption of tacrolimus to the surface of the silicone parts in contact with the fluid path inside the Novelia ® nozzle, similar to what has already been shown for other lipophilic substances like latanoprost, and to a lesser extent, cyclosporine [55]. These variations must, however, be compared to the variable and small quantity actually absorbed by the eye after instillation [56], and they are quite possibly clinically insignificant.…”
Section: Discussionmentioning
confidence: 56%